Mapping the synthetic aperture radar signal processor on a distributed-memory MIMD architecture - Fabbretti, G.; Farina, A.; Laforenza, D.; Vinelli, F. (Parallel computing, 1996)
This paper describes the processing of raw data, gathered with a synthetic aperture radar (SAR), by the parallel computer nCUBE 2 to form an electromagnetic image of the sensed scene. The initial goal of our work has been the evaluation of the use of a Distributed-Memory Multiple-Instruction stream Multiple-Data stream (DM-MIMD) parallel computer for SAR processing, with respect to the use of a conventional monoprocessor RISC workstation. To meet this goal, a study of some algorithms of the radix-2 n class for the one-dimensional (1D) and two-dimensional (2D) FFTs has been conducted. A good algorithm candidate to be parallelized and used as kernel component of our SAR processor has been selected.